A high flatness lithium tantalate wafer and its polishing process

CN120985423BActive Publication Date: 2026-10-13XUZHOU NORMAL UNIVERSITY +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511143277.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-15
Publication Date
2026-10-13
Estimated Expiration
2045-08-15

AI Technical Summary

Technical Problem

[0005]为了解决现有技术中钽酸锂晶片平坦度差和黑化还原不均匀的问题,本申请提供了一种高平整度钽酸锂晶片及其抛光工艺

Benefits of technology

[0028]为了改善钽酸锂晶片平坦度差和黑化还原不均匀的问题,本申请从两方面入手,一是加入了在精抛过程中加入了功能化抛光粉,该功能化抛光粉中含有丰富羟基、吡啶基和柔性链结构,羟基的存在不仅能通过化学吸附在钽酸锂晶片表面形成钝化层,而且各羟基间还能形成氢键网络,减少抛光表面划痕,吡啶基能通过范德华力和氢键作用吸附在钽酸锂表面,进一步减少抛光表面划痕,柔性链结构的存在,在抛光过程中,能够产生弹性形变,将抛光压力更加温和地传递给抛光面,减少抛光表面划痕,二是加入了改性还原剂,改性还原剂中含有TOCNF凝胶,TOCNF凝胶在加热过程中能发生聚合和凝胶化反应,形成交联三维网络机构,可以延缓水蒸气的散发,使得水蒸气大部分锁在复合碳球内,让碳与水蒸气的反应充分,TOCNF凝胶经高温分解后不仅会产生大量的CO2和H2O,而且形成带有孔隙的结构,有助于气体的均匀分布和传输,与复合碳球内部的开放孔道结构协同,进而提高还原反应的均匀性和彻底性。

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The application relates to the field of processing methods of semiconductor devices, and specifically discloses a lithium tantalate wafer with high flatness and a polishing process thereof, which comprises the following steps: step S1, slicing; step S2, grinding; step S3, polishing; step S4, etching; and step S5, blackening reduction; the functional polishing powder and the modified reducing agent are added in the application, the functional polishing powder contains rich hydroxyl groups, pyridyl groups and flexible chain structures, the existence of the hydroxyl groups can not only form a passivation layer on the surface of the lithium tantalate wafer through chemical adsorption, but also form a hydrogen bond network among the hydroxyl groups, the pyridyl groups can be adsorbed on the surface of the lithium tantalate through Van der Waals force and hydrogen bond action, and the existence of the flexible chain structures can produce elastic deformation; the modified reducing agent contains TOCNF gel, the TOCNF gel can not only generate polymerization and gelation reactions in the heating process, but also generate a large amount of CO2 and H2O, so that the problems of poor flatness and uneven blackening reduction of the lithium tantalate wafer are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of semiconductor device processing methods, and more specifically, to a high-flatness lithium tantalate wafer and its polishing process. Background Technology

[0002] Lithium tantalate is a typical soft and brittle multifunctional crystal material. Due to its unique physical properties, such as piezoelectricity, pyroelectricity, ferroelectricity, acousto-optic and electro-optic effects, it has received widespread attention in the fields of aerospace, aviation and commercial optoelectronic products.

[0003] However, lithium tantalate has the following processing defects: low hardness, making it prone to scratches; high toughness, resulting in slow processing speed; and it is easy to generate small-angle wedges and fragments during planar processing, forming sand channels. To prepare high-performance lithium tantalate wafers, existing technologies often employ milling, reactive ion etching, ion milling, and wet etching. Among these, reactive ion etching, ion milling, and wet etching have very low removal rates for lithium tantalate wafers. Simultaneously, oxygen in the wafer reacts with reducing substances in the grinding environment, causing the wafer to turn black. Existing technologies have researched various blackening methods for lithium tantalate. For example, Chinese patent CN100424235C proposes a method of first performing deep reduction treatment on lithium tantalate, lithium niobate, and hydrogen storage metal, and then alternately stacking the deeply reduced wafer with the lithium tantalate wafer to be treated for further reduction treatment. This process not only requires high wafer flatness but also leads to uneven blackening and reduction of the wafer.

[0004] Based on the above statements, this application provides a high-flatness lithium tantalate wafer and its polishing process. Summary of the Invention

[0005] To address the issues of poor flatness and uneven blackening reduction in existing lithium tantalate wafers, this application provides a high-flatness lithium tantalate wafer and its polishing process.

[0006] A polishing process for high-flatness lithium tantalate wafers includes the following steps:

[0007] Step S1, Slicing: Use a slicer to cut the lithium tantalate crystal rod into pre-treated material;

[0008] Step S2, Grinding: Grind the pretreated material obtained in step S1;

[0009] Step S3, Polishing: The abrasive material prepared in step S2 is subjected to coarse polishing and fine polishing in sequence to obtain polishing material;

[0010] Step S4, Etching: The polishing material prepared in step S3 is etched with an etching solution to obtain etched material;

[0011] Step S5, Reduction Blackening: The etched material prepared in step S4 is subjected to reduction blackening. Specifically, the reduction blackening is carried out by reducing the etched material prepared in step S4 for 6-8 hours at a nitrogen flow rate of 6-10 L / min and a temperature of 520-540℃ using an annealing furnace and a modified reducing agent to obtain high-flatness lithium tantalate wafers.

[0012] Preferably, in step S1, the wire speed of the slicer is 400-1000 m / min, and the temperature is 22±2℃.

[0013] Preferably, in step S2, the grinding pressure is 20-60 kg and the temperature is 22±2℃.

[0014] Preferably, in step S3, the pressure is 40-60 kg and the temperature is 22±2℃ during the coarse polishing process, and the pressure is 20-40 kg and the temperature is 22±2℃ during the fine polishing process.

[0015] Preferably, in step S3, the coarse polishing solution is a diamond polishing solution, and the fine polishing solution is a mixture of oxidant, functionalized polishing powder, dispersant and deionized water in a mass ratio of 12-16:6-8:5-9:70-80.

[0016] Preferably, the oxidant is hydrogen peroxide.

[0017] Preferably, the dispersant is alkylphenol polyvinyl ether.

[0018] Preferably, in step S4, the corrosion solution is a mixture of nitric acid solution and hydrofluoric acid solution in a volume ratio of 1.6-2:1, and the temperature is controlled at 96-102℃ and the corrosion treatment time is 12-16 minutes.

[0019] Preferably, in step S5, the TOCNF gel, catalyst, and carbon source are mixed in a mass ratio of 2-4:1:6-8.

[0020] Preferably, the catalyst is nano-alumina or nano-zinc oxide.

[0021] Preferably, the carbon source is graphite powder or activated carbon powder.

[0022] Preferably, the functionalized polishing powder is prepared by the following steps:

[0023] Step A1: Add 2-amino-3-hydroxypyridine to anhydrous DMF, heat to 40-50℃, stir until homogeneous, adjust pH to 9-10, and add a mixture of octenyl succinic anhydride and isopropanol dropwise while stirring, controlling the addition to be completed within 30 minutes. After the addition is completed, heat to 76-82℃ and continue stirring for 6.4-7.2 hours. Adjust pH to neutral, rotary evaporate, wash and dry to obtain trihydroxy monomer. The mass ratio of 2-amino-3-hydroxypyridine, anhydrous DMF and mixture a is 2-4:50-60:16, and the mass ratio of octenyl succinic anhydride and isopropanol in mixture a is 2.2-4.6:40. In the above reaction process, using anhydrous DMF as solvent, the amino group on 2-amino-3-hydroxypyridine undergoes a ring-opening esterification reaction with octenyl succinic anhydride to obtain trihydroxy monomer.

[0024] Step A2: At room temperature and under nitrogen protection, sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, and deionized water are mixed evenly, heated to 66-72℃, potassium persulfate is added, and the temperature is further raised to 78-82℃. The mixture is stirred and reacted for 6.8-7.4 hours to obtain a modified polystyrene emulsion. The mass ratio of sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, deionized water, and potassium persulfate is 0.02-0.04:14-18:0.7-0.8:1.2-1.4:50-60:0.08-0.12. Sodium dodecyl sulfonate is used as an emulsifier, and styrene, p-aminostyrene, and trihydroxy monomer are used as reacting monomers. The modified polystyrene emulsion is prepared by emulsion polymerization.

[0025] Step A3: Add the modified polystyrene emulsion to deionized water, ultrasonically disperse it evenly, add cerium nitrate hexahydrate and potassium fluoride solution, stir evenly, then add hexamethylenetetramine, control the reaction temperature at 74-78℃, stir and react for 2.4-3 hours, cool to room temperature, add polyethylene glycol, continue stirring and react for 16-20 minutes, centrifuge, wash the precipitate, dry, and obtain functionalized polishing powder;

[0026] The modified polystyrene emulsion, deionized water, cerium nitrate hexahydrate, potassium fluoride, hexamethylenetetramine, and polyethylene glycol are in a mass ratio of 4:160-200:1.5:0.04-0.06:2.4-3.2:0.01-0.03, and the potassium fluoride solution has a mass fraction of 5-7%. Using modified polystyrene microspheres as the core, cerium nitrate hexahydrate and hexamethylenetetramine as raw materials, and potassium fluoride as the fluorinating agent, functionalized polishing powder is obtained through co-precipitation.

[0027] In summary, this application has the following beneficial effects:

[0028] To address the issues of poor flatness and uneven blackening reduction in lithium tantalate wafers, this application takes a two-pronged approach. First, functionalized polishing powder is incorporated into the fine polishing process. This powder is rich in hydroxyl groups, pyridine groups, and flexible chain structures. The presence of hydroxyl groups not only allows them to form a passivation layer on the lithium tantalate wafer surface through chemical adsorption, but also enables the formation of hydrogen bond networks between the hydroxyl groups, reducing scratches on the polished surface. Pyridine groups can be adsorbed onto the lithium tantalate surface through van der Waals forces and hydrogen bonding, further reducing scratches. The presence of flexible chain structures allows for elastic deformation during polishing, transmitting polishing pressure more gently. First, the material is applied to the polished surface to reduce scratches. Second, a modified reducing agent is added, which contains TOCNF gel. During heating, TOCNF gel undergoes polymerization and gelation reactions to form a cross-linked three-dimensional network structure. This can delay the release of water vapor, allowing most of the water vapor to be locked inside the composite carbon spheres, thus ensuring a full reaction between carbon and water vapor. After high-temperature decomposition, TOCNF gel not only produces a large amount of CO2 and H2O, but also forms a porous structure, which helps in the uniform distribution and transport of gas. This works synergistically with the open pore structure inside the composite carbon spheres to improve the uniformity and thoroughness of the reduction reaction. Detailed Implementation

[0029] To make the implementation methods of this application easier to understand, the application will be described in detail below with reference to specific embodiments. These embodiments are for illustrative purposes only and are not limited to the application scope of this application.

[0030] The main raw materials and their component contents used in the examples and comparative examples are shown below:

[0031] The diamond polishing slurry is a commercially available product of Danyang Zhongyan Abrasive Materials Technology Co., Ltd., model number PG series diamond abrasive powder, brand name Zhongyan Materials Technology; the TOCNF gel is a commercially available product of Hubei Maidehao Biotechnology Co., Ltd., product number 250330; the nano alumina is a commercially available product of Wuhan Kemike Biomedical Technology Co., Ltd., CAS number 316-46-1; the nano zinc oxide is a commercially available product of Hangzhou Jikang New Materials Co., Ltd., CAS number 1314-13-2, model number [missing information]. SS-Z20 uses Fenghua brand 80-mesh graphite powder (sold by Shijiazhuang Fenghua Mineral Products Co., Ltd., Hebei Province), 200-mesh powdered activated carbon (sold by Gongyi Jinding Powder Metallurgy Co., Ltd., Henan Province), polyvinyl alcohol (sold by Inner Mongolia Meiguan Environmental Protection Products Co., Ltd., CAS number 9002-89-5), and aluminosilicate gel (sold by Luoyang Yiyuan New Materials Co., Ltd., model XH52501NLAUY, item number HH5250BSAK5J).

[0032] Preparation Examples 1-3 and Comparative Preparation Examples 1-2 provide a functionalized polishing powder.

[0033] Preparation Example 1

[0034] This preparation example provides a functionalized polishing powder, which is prepared by the following steps:

[0035] Step A1: Add 2-amino-3-hydroxypyridine to anhydrous DMF, heat to 40°C, control the stirring speed at 560 rpm, stir for 12 min until homogeneous, adjust the pH to 9 with 0.1% sodium bicarbonate aqueous solution, and add octenyl succinic anhydride and isopropanol mixture a dropwise while stirring, controlling the addition to be completed within 30 min. After the addition is completed, heat to 76°C, continue stirring and reacting for 6.4 h, adjust the pH to neutral, control the rotary evaporation temperature at 82°C, and rotary evaporate until anhydrous DMF is removed. Then wash with anhydrous ethanol and deionized water three times each, and dry at 60°C to constant weight to obtain the trihydroxy monomer. The mass ratio of 2-amino-3-hydroxypyridine, anhydrous DMF and mixture a is 2:50:16, and the mass ratio of octenyl succinic anhydride and isopropanol in mixture a is 2.2:40.

[0036] Step A2: At room temperature, under nitrogen protection, sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, and deionized water are stirred at 280 rpm for 12 min until uniformly mixed. The temperature is raised to 66°C, potassium persulfate is added, the stirring speed is adjusted to 420 rpm, and the temperature is further raised to 78°C. The mixture is stirred and reacted for 6.8 h to obtain a modified polystyrene emulsion. The mass ratio of sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, deionized water, and potassium persulfate is 0.02:14:0.7:1.2:50:0.08.

[0037] Step A3: Add the modified polystyrene emulsion to deionized water and sonicate for 14 minutes at an ultrasonic frequency of 25 kHz and an ultrasonic power of 400 W until homogeneous. Add cerium nitrate hexahydrate and potassium fluoride solution, and stir for 20 minutes at a speed of 550 rpm until homogeneous. Then add hexamethylenetetramine, control the reaction temperature at 74℃, maintain the speed, and continue stirring for 2.4 hours. Cool to room temperature, add polyethylene glycol, and stir for 16 minutes. Centrifuge to separate the precipitate, wash it three times each with anhydrous ethanol and deionized water, and dry it at 60℃ to obtain functionalized polishing powder. The mass ratio of modified polystyrene emulsion, deionized water, cerium nitrate hexahydrate, potassium fluoride, hexamethylenetetramine, and polyethylene glycol is 4:160:1.5:0.04:2.4:0.01, and the mass fraction of potassium fluoride solution is 5%.

[0038] Preparation Example 2

[0039] This preparation example provides a functionalized polishing powder, which is prepared by the following steps:

[0040] Step A1: Add 2-amino-3-hydroxypyridine to anhydrous DMF, heat to 45°C, control the stirring speed at 580 rpm, stir for 14 min until homogeneous, adjust the pH to 9.5 with 0.3% sodium bicarbonate aqueous solution, and add octenyl succinic anhydride and isopropanol mixture a dropwise while stirring, controlling the addition to be completed within 30 min. After the addition is completed, heat to 79°C, continue stirring and react for 6.8 h, adjust the pH to neutral, control the rotary evaporation temperature at 84°C, and rotary evaporate until anhydrous DMF is removed. Then wash with anhydrous ethanol and deionized water 4 times each, and dry at 64°C to constant weight to obtain the trihydroxy monomer. The mass ratio of 2-amino-3-hydroxypyridine, anhydrous DMF and mixture a is 3:55:16, and the mass ratio of octenyl succinic anhydride and isopropanol in mixture a is 3.4:40.

[0041] Step A2: At room temperature, under nitrogen protection, sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, and deionized water are stirred at 290 rpm for 14 min until homogeneous. The temperature is raised to 69°C, potassium persulfate is added, and the temperature is further raised to 80°C. The stirring speed is adjusted to 440 rpm, and the reaction is continued for 7.1 h to obtain a modified polystyrene emulsion. The mass ratio of sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, deionized water, and potassium persulfate is 0.03:16:0.75:1.3:55:0.1.

[0042] Step A3: Add the modified polystyrene emulsion to deionized water and sonicate for 16 minutes at an ultrasonic frequency of 30 kHz and an ultrasonic power of 450 W until homogeneous. Add cerium nitrate hexahydrate and potassium fluoride solution, and stir for 22 minutes at a speed of 580 rpm until homogeneous. Then add hexamethylenetetramine, control the reaction temperature at 76℃, maintain the speed, and continue stirring for 2.7 hours. Cool to room temperature, add polyethylene glycol, and stir for 18 minutes. Centrifuge to separate the precipitate, wash it four times each with anhydrous ethanol and deionized water, and dry it at 62℃ to obtain functionalized polishing powder. The mass ratio of modified polystyrene emulsion, deionized water, cerium nitrate hexahydrate, potassium fluoride, hexamethylenetetramine, and polyethylene glycol is 4:180:1.5:0.05:2.8:0.02, and the mass fraction of potassium fluoride solution is 6%.

[0043] Preparation Example 3

[0044] This preparation example provides a functionalized polishing powder, which is prepared by the following steps:

[0045] Step A1: Add 2-amino-3-hydroxypyridine to anhydrous DMF, heat to 50°C, control the stirring speed at 600 rpm, stir for 16 min until homogeneous, adjust the pH to 10 with 0.5% sodium bicarbonate aqueous solution, and add octenyl succinic anhydride and isopropanol mixture a dropwise while stirring, controlling the addition to be completed within 30 min. After the addition is completed, heat to 82°C, continue stirring and reacting for 7.2 h, adjust the pH to neutral, control the rotary evaporation temperature at 86°C, and rotary evaporate until anhydrous DMF is removed. Then wash with anhydrous ethanol and deionized water 5 times each, and dry at 68°C to constant weight to obtain the trihydroxy monomer. The mass ratio of 2-amino-3-hydroxypyridine, anhydrous DMF and mixture a is 4:60:16, and the mass ratio of octenyl succinic anhydride and isopropanol in mixture a is 4.6:40.

[0046] Step A2: At room temperature, under nitrogen protection, sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, and deionized water are stirred at 300 rpm for 16 minutes until homogeneous. The temperature is raised to 72°C, potassium persulfate is added, and the temperature is further raised to 82°C. The stirring speed is adjusted to 460 rpm, and the reaction is continued for 7.4 hours to obtain a modified polystyrene emulsion. The mass ratio of sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, deionized water, and potassium persulfate is 0.04:18:0.8:1.4:60:0.12.

[0047] Step A3: Add the modified polystyrene emulsion to deionized water and sonicate for 18 minutes at an ultrasonic frequency of 35 kHz and an ultrasonic power of 500 W until homogeneous. Add cerium nitrate hexahydrate and potassium fluoride solution, and stir for 24 minutes at a speed of 610 rpm until homogeneous. Then add hexamethylenetetramine, control the reaction temperature at 78℃, maintain the speed, and continue stirring for 3 hours. Cool to room temperature, add polyethylene glycol, and stir for 20 minutes. Centrifuge to separate the precipitate, wash it 5 times each with anhydrous ethanol and deionized water, and dry it at 64℃ to obtain functionalized polishing powder. The mass ratio of modified polystyrene emulsion, deionized water, cerium nitrate hexahydrate, potassium fluoride, hexamethylenetetramine, and polyethylene glycol is 4:200:1.5:0.06:3.2:0.03, and the mass fraction of potassium fluoride solution is 7%.

[0048] Comparative Preparation Example 1

[0049] This comparative preparation example provides a functionalized polishing powder, which is prepared by the following steps:

[0050] Step A1: Add 2-amino-3-hydroxypyridine to anhydrous DMF, heat to 40°C, control the stirring speed at 560 rpm, stir for 12 min until homogeneous, adjust the pH to 9 with 0.1% sodium bicarbonate aqueous solution, and add a mixture of itaconic anhydride and isopropanol dropwise while stirring, controlling the addition to be completed within 30 min. After the addition is completed, heat to 76°C, continue stirring and react for 6.4 h, adjust the pH to neutral, control the rotary evaporation temperature at 82°C, and rotary evaporate until anhydrous DMF is removed. Then wash three times each with anhydrous ethanol and deionized water, and dry at 60°C to constant weight to obtain the trihydroxy monomer. The mass ratio of 2-amino-3-hydroxypyridine, anhydrous DMF and mixture a is 2:50:16, and the mass ratio of itaconic anhydride and isopropanol in mixture a is 2.2:40.

[0051] Step A2: At room temperature, under nitrogen protection, sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, and deionized water are stirred at 280 rpm for 12 min until uniformly mixed. The temperature is raised to 66°C, potassium persulfate is added, the stirring speed is adjusted to 420 rpm, and the temperature is further raised to 78°C. The mixture is stirred and reacted for 6.8 h to obtain a modified polystyrene emulsion. The mass ratio of sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, deionized water, and potassium persulfate is 0.02:14:0.7:1.2:50:0.08.

[0052] Step A3: Add the modified polystyrene emulsion to deionized water and sonicate for 14 minutes at an ultrasonic frequency of 25 kHz and an ultrasonic power of 400 W until homogeneous. Add cerium nitrate hexahydrate and potassium fluoride solution, and stir for 20 minutes at a speed of 550 rpm until homogeneous. Then add hexamethylenetetramine, control the reaction temperature at 74℃, maintain the speed, and continue stirring for 2.4 hours. Cool to room temperature, add polyethylene glycol, and stir for 16 minutes. Centrifuge to separate the precipitate, wash it three times each with anhydrous ethanol and deionized water, and dry it at 60℃ to obtain functionalized polishing powder. The mass ratio of modified polystyrene emulsion, deionized water, cerium nitrate hexahydrate, potassium fluoride, hexamethylenetetramine, and polyethylene glycol is 4:160:1.5:0.04:2.4:0.01, and the mass fraction of potassium fluoride solution is 5%.

[0053] Comparative Preparation Example 2

[0054] This comparative preparation example provides a functionalized polishing powder, which is prepared by the following steps:

[0055] Step A1: Add 4-aminophenol to anhydrous DMF, heat to 40℃, control the stirring speed at 560 rpm, stir for 12 min until homogeneous, adjust the pH to 9 with 0.1% sodium bicarbonate aqueous solution, and add octenyl succinic anhydride and isopropanol mixture a dropwise while stirring, controlling the addition to be completed within 30 min. After the addition is completed, heat to 76℃, continue stirring and reacting for 6.4 h, adjust the pH to neutral, control the rotary evaporation temperature at 82℃, and rotary evaporate until anhydrous DMF is removed. Then wash with anhydrous ethanol and deionized water three times each, and dry at 60℃ to constant weight to obtain trihydroxy monomer. The mass ratio of 4-aminophenol, anhydrous DMF and mixture a is 2:50:16, and the mass ratio of octenyl succinic anhydride and isopropanol in mixture a is 2.2:40.

[0056] Step A2: At room temperature, under nitrogen protection, sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, and deionized water are stirred at 280 rpm for 12 min until uniformly mixed. The temperature is raised to 66°C, potassium persulfate is added, the stirring speed is adjusted to 420 rpm, and the temperature is further raised to 78°C. The mixture is stirred and reacted for 6.8 h to obtain a modified polystyrene emulsion. The mass ratio of sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, deionized water, and potassium persulfate is 0.02:14:0.7:1.2:50:0.08.

[0057] Step A3: Add the modified polystyrene emulsion to deionized water and sonicate for 14 minutes at an ultrasonic frequency of 25 kHz and an ultrasonic power of 400 W until homogeneous. Add cerium nitrate hexahydrate and potassium fluoride solution, and stir for 20 minutes at a speed of 550 rpm until homogeneous. Then add hexamethylenetetramine, control the reaction temperature at 74℃, maintain the speed, and continue stirring for 2.4 hours. Cool to room temperature, add polyethylene glycol, and stir for 16 minutes. Centrifuge to separate the precipitate, wash it three times each with anhydrous ethanol and deionized water, and dry it at 60℃ to obtain functionalized polishing powder. The mass ratio of modified polystyrene emulsion, deionized water, cerium nitrate hexahydrate, potassium fluoride, hexamethylenetetramine, and polyethylene glycol is 4:160:1.5:0.04:2.4:0.01, and the mass fraction of potassium fluoride solution is 5%.

[0058] Examples 1-3 and Comparative Examples 1-3 provide a high-flatness lithium tantalate wafer and its polishing process.

[0059] Example 1

[0060] This embodiment provides a polishing process for high-flatness lithium tantalate wafers, including the following steps:

[0061] Step S1, Slicing: Under the conditions of a wire speed of 400m / min and a temperature of 20℃, the lithium tantalate crystal rod is sliced ​​into pretreated material with a thickness of 200μm using a slicing machine;

[0062] Step S2, Grinding: Grind the pretreated material prepared in step S1 using a CY-400PC double-sided grinding mill, controlling the grinding pressure at 20Kg and the temperature at 20℃.

[0063] Step S3, Polishing: The abrasive material prepared in step S2 is subjected to coarse polishing and fine polishing in sequence to obtain polishing material. Specifically, the coarse polishing process is to polish the lithium tantalate wafer with a coarse polishing machine and diamond polishing liquid at a pressure of 40Kg and a temperature of 20℃, so that the roughness reaches 0.05μm and the thickness uniformity is within 1μm. Specifically, the fine polishing process is to polish the lithium tantalate wafer with a fine polishing machine and fine polishing liquid at a pressure of 20Kg and a temperature of 22±2℃, so that the roughness reaches below 1nm, with a mirror effect and no stress. The fine polishing liquid is composed of hydrogen peroxide, functionalized polishing powder prepared in preparation example 1, alkylphenol polyvinyl ether and deionized water in a mass ratio of 12:6:5:70.

[0064] Step S4, Etching: The polishing material prepared in step S3 is etched with an etching solution to obtain etched material. The etching solution is a mixture of 68% nitric acid and 40% hydrofluoric acid in a volume ratio of 1.6:1. During the etching process, the temperature is controlled at 96℃ and the etching time is 12min.

[0065] Step S5, Reduction Blackening: The etched material prepared in step S4 is subjected to reduction blackening. Specifically, the etched material prepared in step S4 is reduced for 6 hours at a nitrogen flow rate of 6 L / min and a temperature of 520℃ using an annealing furnace and a modified reducing agent to obtain high-flatness lithium tantalate wafers. The modified reducing agent is composed of TOCNF gel, nano-alumina and graphite powder in a mass ratio of 2:1:6, which are ball-milled until uniform, and then evenly sprinkled in a reducing agent loading box and placed at the bottom of the annealing furnace. The ball milling conditions are: ball milling speed of 240 rpm, ball milling time of 2 hours, and ball-to-material ratio of 6:1.

[0066] Example 2

[0067] This embodiment provides a polishing process for high-flatness lithium tantalate wafers, including the following steps:

[0068] Step S1, Slicing: Under the conditions of a wire speed of 700m / min and a temperature of 22℃, the lithium tantalate crystal rod is sliced ​​into pretreated material with a thickness of 220μm using a slicing machine;

[0069] Step S2, Grinding: Grind the pretreated material prepared in step S1 using a CY-400PC double-sided grinding mill, controlling the grinding pressure at 40Kg and the temperature at 22℃.

[0070] Step S3, Polishing: The abrasive material prepared in step S2 is subjected to coarse polishing and fine polishing in sequence to obtain polishing material. Specifically, the coarse polishing process is to polish the lithium tantalate wafer with a coarse polishing machine and diamond polishing liquid at a pressure of 50Kg and a temperature of 22℃, so that the roughness reaches 0.05μm and the thickness uniformity is within 1μm. Specifically, the fine polishing process is to polish the lithium tantalate wafer with a fine polishing machine and fine polishing liquid at a pressure of 40Kg and a temperature of 24℃, so that the roughness reaches below 1nm, with a mirror effect and no stress. The fine polishing liquid is composed of hydrogen peroxide, functionalized polishing powder prepared in preparation example 2, alkylphenol polyvinyl ether and deionized water in a mass ratio of 14:7:7:75.

[0071] Step S4, Etching: The polishing material prepared in step S3 is etched with an etching solution to obtain etched material. The etching solution is a mixture of 68% nitric acid and 40% hydrofluoric acid in a volume ratio of 1.8:1. During the etching process, the temperature is controlled at 99℃ and the etching time is 14min.

[0072] Step S5, Reduction Blackening: The etched material prepared in step S4 is subjected to reduction blackening. Specifically, the etched material prepared in step S4 is reduced for 7 hours at a nitrogen flow rate of 8 L / min and a temperature of 530℃ using an annealing furnace and a modified reducing agent to obtain high-flatness lithium tantalate wafers. The modified reducing agent is composed of TOCNF gel, nano zinc oxide and activated carbon powder, which are ball-milled in a mass ratio of 3:1:7 until uniform. The mixture is then evenly sprinkled in a reducing agent loading box and placed at the bottom of the annealing furnace. The ball milling conditions are: ball milling speed of 280 rpm, ball milling time of 2.5 hours, and ball-to-material ratio of 7:1.

[0073] Example 3

[0074] This embodiment provides a polishing process for high-flatness lithium tantalate wafers, including the following steps:

[0075] Step S1, Slicing: Under the conditions of a wire speed of 1000m / min and a temperature of 24℃, the lithium tantalate crystal rod is sliced ​​into pretreated material with a thickness of 240μm using a slicing machine;

[0076] Step S2, Grinding: Grind the pretreated material prepared in step S1 using a CY-400PC double-sided grinding mill, controlling the grinding pressure at 60Kg and the temperature at 24℃.

[0077] Step S3, Polishing: The abrasive material prepared in step S2 is subjected to coarse polishing and fine polishing in sequence to obtain polishing material. Specifically, the coarse polishing process is to polish the lithium tantalate wafer with a coarse polishing machine and diamond polishing liquid at a pressure of 60Kg and a temperature of 24℃, so that the roughness reaches 0.05μm and the thickness uniformity is within 1μm. Specifically, the fine polishing process is to polish the lithium tantalate wafer with a fine polishing machine and fine polishing liquid at a pressure of 60Kg and a temperature of 24℃, so that the roughness reaches below 1nm, with a mirror effect and no stress. The fine polishing liquid is composed of hydrogen peroxide, functionalized polishing powder prepared in preparation example 3, alkylphenol polyvinyl ether and deionized water in a mass ratio of 16:8:9:80.

[0078] Step S4, Etching: The polishing material prepared in step S3 is etched with an etching solution to obtain etched material. The etching solution is a mixture of 68% nitric acid and 40% hydrofluoric acid in a volume ratio of 2:1. During the etching process, the temperature is controlled at 102℃ and the etching time is 16min.

[0079] Step S5, Reduction Blackening: The etched material prepared in step S4 is subjected to reduction blackening. Specifically, the etched material prepared in step S4 is reduced for 8 hours at a nitrogen flow rate of 10 L / min and a temperature of 540℃ using an annealing furnace and a modified reducing agent to obtain high-flatness lithium tantalate wafers. The modified reducing agent is made by ball milling TOCNF gel, nano-alumina and graphite powder in a mass ratio of 4:1:8 until uniform, and then evenly sprinkled in a reducing agent loading box and placed at the bottom of the annealing furnace. The ball milling conditions are: ball milling speed of 320 rpm, ball milling time of 3 hours, and ball-to-material ratio of 8:1.

[0080] Comparative Example 1

[0081] Comparative Example 1 is the same as Example 1, except that the functional polishing powder in Example 1 is replaced with the functional polishing powder prepared in Comparative Preparation Example 1.

[0082] Comparative Example 2

[0083] Comparative Example 2 is the same as Example 1, except that the functional polishing powder in Example 1 is replaced with the functional polishing powder prepared in Comparative Preparation Example 2.

[0084] Comparative Example 3

[0085] Comparative Example 3 is the same as Example 1, except that the TOCNF gel in the modified reducing agent of Example 1 is replaced with an equal mass of silica-alumina gel.

[0086] Performance testing

[0087] 1. The glass cross-sections before and after polishing were characterized using a JSM-6700F field emission scanning electron microscope (JEOL Ltd., Japan). Changes in flatness were observed before and after polishing. Polished glass substrates were ultrasonically cleaned and then dried in a drying oven before analysis. Surface roughness refers to the small spacing and minute peak-valley unevenness of a machined surface. Ra is the average roughness, referring to a finer surface feature within a smaller spatial wavelength range. The Ra of the polished glass surface was measured using a JB-4C precision roughness tester from Hömmel GmbH, Germany. The specific test results are shown in Table 1 below.

[0088] 2. The transmittance of lithium tantalate wafers prepared in Examples 1-3 and Comparative Examples 1-3 was tested under exposure light source with wavelengths from 350 nm to 450 nm, with untreated lithium tantalate wafers serving as a blank group. The specific test results are shown in Table 1 below:

[0089] Table 1 Performance Test Results

[0090] Example 1 0.04 0.180 0.084 Example 2 0.01 0.181 0.082 Example 3 0.03 0.180 0.085 Comparative Example 1 0.07 0.181 0.156 Comparative Example 2 0.06 0.181 0.163 Comparative Example 3 0.15 0.181 0.106 Blank group 75.3 / /

[0091] Compared with Comparative Examples 1-3, the lithium tantalate wafers prepared in Examples 1-3 have better transmittance and flatness. This shows that the lithium tantalate wafer polishing process provided in this application can effectively solve the problems of poor flatness and uneven blackening reduction of lithium tantalate wafers in the prior art.

[0092] This specific embodiment is merely an explanation of this application and is not intended to limit it. After reading this specification, those skilled in the art can make modifications to this embodiment without contributing any inventive step, but such modifications are protected by patent law as long as they fall within the scope of the claims of this application.

Claims

1. A polishing process for high-flatness lithium tantalate wafers, characterized in that, Includes the following steps: Step S1, Slicing: Use a slicer to cut the lithium tantalate crystal rod into pre-treated material; Step S2, Grinding: Grind the pretreated material obtained in step S1; Step S3, Polishing: The abrasive material prepared in step S2 is subjected to coarse polishing and fine polishing in sequence to obtain polishing material; Step S4, Etching: The polishing material prepared in step S3 is etched with an etching solution to obtain etched material; Step S5, Reduction Blackening: The etched material prepared in step S4 is subjected to reduction blackening to obtain high-flatness lithium tantalate wafers. In step S3, the fine polishing process uses a fine polishing solution, which is a mixture of oxidant, functionalized polishing powder, dispersant and deionized water in a mass ratio of 12-16:6-8:5-9:70-80. The functionalized polishing powder is first prepared by ring-opening esterification of 2-amino-3-hydroxypyridine and octenyl succinic anhydride to obtain a trihydroxy monomer, which is then subjected to emulsion polymerization with styrene and p-aminostyrene to obtain a modified polystyrene emulsion. Finally, it is prepared by co-precipitation with cerium nitrate hexahydrate.

2. The polishing process for a high-flatness lithium tantalate wafer according to claim 1, characterized in that, The functionalized polishing powder is prepared by the following steps: Step A1: Add 2-amino-3-hydroxypyridine to anhydrous DMF, heat to 40-50℃, stir until homogeneous, adjust pH to 9-10, and add a mixture of octenyl succinic anhydride and isopropanol dropwise while stirring, controlling the addition to be completed within 30 minutes. After the addition is completed, heat to 76-82℃, continue stirring for 6.4-7.2 hours, adjust pH to neutral, rotary evaporate, wash and dry to obtain trihydroxy monomer; Step A2: At room temperature, under nitrogen protection, sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer and deionized water are mixed evenly, heated to 66-72℃, potassium persulfate is added, and the temperature is further raised to 78-82℃. The mixture is stirred and reacted for 6.8-7.4 hours to obtain modified polystyrene emulsion. Step A3: Add the modified polystyrene emulsion to deionized water, ultrasonically disperse it evenly, add cerium nitrate hexahydrate and potassium fluoride solution, stir evenly, then add hexamethylenetetramine, control the reaction temperature at 74-78℃, stir and react for 2.4-3 hours, cool to room temperature, add polyethylene glycol, continue stirring and reacting for 16-20 minutes, centrifuge, wash the precipitate, dry, and obtain functionalized polishing powder.

3. The polishing process for a high-flatness lithium tantalate wafer according to claim 2, characterized in that, In step A1, the mass ratio of 2-amino-3-hydroxypyridine, anhydrous DMF, and mixture a is 2-4:50-60:16, and the mass ratio of octenyl succinic anhydride and isopropanol in mixture a is 2.2-4.6:

40.

4. The polishing process for a high-flatness lithium tantalate wafer according to claim 2, characterized in that, In step A2, the mass ratio of sodium dodecyl sulfonate, styrene, p-aminostyrene, trihydroxy monomer, deionized water, and potassium persulfate is 0.02-0.04: 14-18: 0.7-0.8: 1.2-1.4: 50-60: 0.08-0.

12.

5. The polishing process for a high-flatness lithium tantalate wafer according to claim 2, characterized in that, In step A3, the mass ratio of modified polystyrene emulsion, deionized water, cerium nitrate hexahydrate, potassium fluoride, hexamethylenetetramine, and polyethylene glycol is 4:160-200:1.5:0.04-0.06:2.4-3.2:0.01-0.03, and the mass fraction of potassium fluoride solution is 5-7%.

6. The polishing process for a high-flatness lithium tantalate wafer according to claim 1, characterized in that, In step S1, the wire speed of the slicing machine is 400-1000 m / min, and the temperature is 22℃±2℃.

7. The polishing process for a high-flatness lithium tantalate wafer according to claim 1, characterized in that, In step S2, the grinding pressure is 20-60 kg and the temperature is 22±2℃.

8. The polishing process for a high-flatness lithium tantalate wafer according to claim 1, characterized in that, In step S3, during the coarse polishing process, the pressure is 40-60 kg and the temperature is 22±2℃, while during the fine polishing process, the pressure is 20-40 kg and the temperature is 22±2℃.

9. The polishing process for a high-flatness lithium tantalate wafer according to claim 1, characterized in that, In step S4, the corrosion solution is a mixture of nitric acid solution and hydrofluoric acid solution in a volume ratio of 1.6-2:

1. During the corrosion process, the temperature is controlled at 96-102℃ and the corrosion treatment time is 12-16 minutes.

10. A high-flatness lithium tantalate wafer obtained by the polishing process of the high-flatness lithium tantalate wafer according to any one of claims 1-9.

Citation Information

Patent Citations

  • Process for producing lithium tantalate crystal

    CN100424235C

  • Machining method of large-sized ultrathin high-precision lithium niobate wafer

    CN112621392A

  • Precision polishing agent composition

    JP2015227410A